Engaged food science: Connecting K‐8 learners to food science while engaging graduate students in science communication. Issue 1 (6th December 2020) - Macbeth, Alexandra J.; Zurier, Hannah S.; Atkins, Erin; Nugen, Sam R.; Goddard, Julie M.
Abstract: Connecting the public to concepts in science, technology, engineering, and mathematics (STEM) is an essential for technological advancement and inspiring future scientists, impacting both the communicator and the audience's understanding of scientific topics. Without proper communication of scientific knowledge, acceptance and implementation of new technologies can be hindered. Additionally, increasing public awareness about current scientific issues through STEM engagement permits more informed policy and consumer choices, especially in the field of food science where many new food technologies are met with initial resistance by the consuming public. Here, we describe an event that introduced topics in food science to the nonexpert public, including K‐8th grade participants and their adult caregivers in an informal learning environment. This program consists of six activities that collectively introduce three areas in food science: food chemistry, food microbiology, and process engineering. Protocols are provided for each activity including a materials list (with the option to scale up or down according to event duration, event space allowances, and number of participants), learning objectives and discussion points that are adaptable to different age groups, event spaces, or budgets. Each activity has a participatory component to ensure both audience member and instructor engagement. A program designed for food science communication empowers young scientific minds to better understand complex scientific topics and could inspire them to envision a possible career in STEM fields, with the additional benefit of providing graduate students an exciting medium through which they may practice their science communication skills, potentially benefiting not only their personal academic and professional skills but also broader societal needs.